The microbial contaminants of plant-based meat analogues from the retail market - Dušková, Marta; Dorotíková, Kateřina; Bartáková, Klára; Králová, Michaela; Šedo, Ondrej; Kameník, Josef (International journal of food microbiology, 2024)
The aim of the study was to analyse the key microbial contaminants of plant-based meat analogues (PBMA) from retail. A total of 43 samples of PBMAs (12 frozen/31 chilled) in the "ready-to-cook" category, such as hamburgers, meatballs or breaded imitation steaks were purchased in retail stores in the Czech Republic in summer (n = 21) and autumn 2022 (n = 22). The detected indicator bacteria (total viable count, lactic acid bacteria, Enterobacteriaceae, yeasts, moulds) had relatively low values in the analysed PBMA samples and only rarely reached levels of 7 log CFU/g. E. coli, STEC and coagulase-positive staphylococci were not detected by isolation from plates in any of analysed samples. Mannitol positive Bacillus spp. were isolated from almost half of the analysed samples of the PBMA. B. cereus sensu lato was isolated from 3 samples by isolation from plates, and after enrichment in 35 samples (81 %). Clostridium perfringens could not be detected by isolation from plates, nevertheless after multiplication, it was detected in 21 % of samples. Analyses of PBMA samples revealed considerable variability in microbial quality. The presence of spore-forming bacteria with the potential to cause foodborne diseases is alarming. However, to evaluate the risks, further research focused on the possibilities of growth under different conditions of culinary treatment and preservation is needed.
Keywords: masné výrobky; Bacillus cereus; Clostridium perfringens; počet mikrobiálních kolonií; Czech Republic; kontaminace potravin; Meat Substitutes; Food Microbiology; maso; Spore-forming bacteria; náhražky masa; Meat; Plant protein; Meat Products; potravinářská mikrobiologie; houby; Meat alternatives; Česká republika; Bacteria; Food Contamination; Colony Count, Microbial; Fungi